Risposte biologiche delle Corallinaceae ai cambiamenti climatici globali e come utilizzarle nell'insegnamento nella scuola secondaria di primo grado (scuola media).Biological response of the Corallinaceae to global climate change and how to use it in teaching at middle school. - BRADASSI, FULVIA; CUMANI, FRANCESCO; BRESSAN, GUIDO (ISPRA, Serie Atti 2010, 2010)
The rising of atmospheric CO2 partial pressure moves marine water pH onto a lower grade. Many marine organisms, that use CaCO3 to build their skeletons, seem to be damaged by Ocean Acidification; especially shallow water ecosystems are at risk. A study on juvenile thalli of calcareous red algae was carried out in a microcosm experiment underdifferent acidic conditions. The encouraging preliminary result suggested taking the experience to educational system: a partnership with a middle school was established to fill the gap between research and school. An experimental course on global climate change and ocean acidification was offered to 14 years-old pupils. The course, experimentally based on calcareous red algae, represents not only a way to spread knowledge on global climatic change among the young, but also a tool to measure how much new methods of teaching can improve scientific knowledge and skills at school level.